2012
DOI: 10.1002/humu.22093
|View full text |Cite
|
Sign up to set email alerts
|

Correlation assessment among clinical phenotypes, expression analysis and molecular modeling of 14 novel variations in the human galactose-1-phosphate uridylyltransferase gene

Abstract: Galactose-1-phosphate uridylyltransferase (GALT) catalyses the conversion of galactose-1-phosphate to UDP-galactose, a key step in the galactose metabolism. Deficiency of GALT activity in humans caused by deleterious variations in the GALT gene can cause a potentially lethal disease called Classic Galactosemia. In this study, we selected 14 novel nucleotide sequence changes in the GALT genes found in galactosemic patients for expression analysis and molecular modeling. Several variants showed decreased levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…In fact, even those variations with no apparent effects on the static model could have caused perturbations in the protein's structure and dynamics. One of the variations with no predicted structural effects (p.Val168Met) is very similar to another one (p.Val168Leu) that showed no effects in the static model, but showed alterations when submitted to a molecular dynamics simulation protocol [23]. Probably, a similar effect could be argued also for the variations characterized in this work.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In fact, even those variations with no apparent effects on the static model could have caused perturbations in the protein's structure and dynamics. One of the variations with no predicted structural effects (p.Val168Met) is very similar to another one (p.Val168Leu) that showed no effects in the static model, but showed alterations when submitted to a molecular dynamics simulation protocol [23]. Probably, a similar effect could be argued also for the variations characterized in this work.…”
Section: Discussionmentioning
confidence: 65%
“…The high percentage of variations predicted to have a negative impact on the overall stability of GALT enzyme is in line with our previous observations [13] (to date, only 1 variation included in GALT Prot database was predicted not to affect protein stability, and only 4 variations are predicted to increase the stability of the protein). Moreover, in a recent characterization of other novel GALT variations [23], mutant proteins were expressed in E. coli and purified, and most of them showed solubility problems and/or reduced expression, thus supporting the idea that stability is a main issue in GALT variants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is of note that various cofactors and modifications can alter a metabolic enzyme’s turnover and stability, with functional association to disease (38). As renewed interest in the mechanistic basis of galactosemia has shown that disease-associated mutants exert their effects on misfolding through affecting expression (39), solubility (33,40), stability (31,40,41) and aggregation tendency (31) of hGALT, it is critical to understand the contribution of these factors. The previous lack of consideration of the effects of covalent modification by UMP and divalent metal binding has been in part due to the absence of a crystal structure of the human protein.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients present with feeding difficulties, failure to thrive, liver disease, cataracts, encephalopathy and sepsis. Early diagnosis and treatment improve the prognosis in patients with classic galactosemia (1)(2)(3). Regarding endocrine abnormalities in classic galactosemia, female hypergonadotropic hypogonadism has often been reported (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%